Blood pressure measurement device selection in low‐resource settings: Challenges, compromises, and routes to progress. Issue 5 (29th April 2020) - Brady, Tammy M.; Padwal, Raj; Blakeman, Drew E.; Farrell, Margaret; Frieden, Thomas R.; Kaur, Prabhdeep; Moran, Andrew E.; Jaffe, Marc G.
Abstract: High blood pressure (BP) is the single leading preventable cardiovascular disease (CVD) risk factor across the world. In order to decrease the global burden of CVD, broad hypertension screening programs that facilitate early hypertension diagnosis and treatment are essential. Accurate BP devices are a key element of hypertension control programs. With the overwhelming number of devices available now on the market, most of which have not been tested for accuracy, it can be challenging to select the optimal BP measurement device for clinical settings. This review details essential factors to consider when selecting a good‐quality BP device, particularly for use in low‐resource settings. Barriers to the procurement and use of good‐quality devices are reviewed and practical solutions proposed.